The Effectiveness of Cognitive Reflection and Re-structurization on Career Decision Making of High School Students - Wagimin Wagimin; Johana Endang Prawitasari; Dany Munindyah Handarini; Triyono Triyono (Pascasarjana UM, 2015)
Keefektifan Refleksi dan Penstrukturan Ulang Kognitif pada Pengambilan Keputusan Karier Siswa SMAAbstract: This study aimed at examining the effectiveness of reflection and cognitive restructuring to improve high school students’ career decision making based on cognitive information processing (CIP) model. The experimental design with RCTs model was employed for this study where 40 stu-dents assigned to be the experimental group members and 40 students of others assigned to be the control group members. The developed career decision making sub-skills were: self-knowledge, oc-cupation knowledge, communication, analysis, synthesis, valuing, execution, and executive proces-sing. The result of this study showed the reflection and cognitive restructuring were effective for im-proving the high school students’ career decision making. It was because after the treatment, there was a significant difference in students’ career decision making between those who were in the ex-perimental groups and in the control groups. The experimental group members had mean score high-er than the control group’s. The controlled trials information also supported that reflection and cog-nitive restructuring were effective to improve the high school students’ career decision making.Key Words: career decision making, CIP model, reflection, cognitive restructuringAbstrak: Penelitian ini bertujuan untuk menguji keefektifan refleksi dan penstrukturan ulang kognitif guna meningkatkan pengambilan keputusan karier siswa SMA berdasarkan model PIK. Penelitian eksperimen ini menggunakan rancangan RCTs, dan subjek 40 orang siswa sebagai kelompok eksperi-men dan 40 sebagai kelompok kontrol. Sub-kemampuan pengambilan keputusan karier model PIK yang dikembangkan meliputi: memahami diri, memahami pilihan pekerjaan, komunikasi, analisis, sinte-sis, penilaian, pelaksanaan, dan proses pelaksanaan. Hasil penelitian menunjukkan bahwa ada perbeda-an kemampuan pengambilan keputusan karier antara siswa kelompok eksperimen dan kelompok kon-trol di mana kelompok eksperimen memiliki nilai rata-rata yang lebih tinggi. Informasi controlled trials menguatkan juga bahwa refleksi dan penstrukturan ulang kognitif efektif untuk meningkatkan kemampuan pengambilan keputusan karier siswa SMA. Kata kunci: pengambilan keputusan karier, model PIK, refleksi, penstrukturan ulang kognitif